53.9k views
1 vote
Combine like terms to create an equivalent expression -1/2(-3y+10)

User Wheezil
by
4.7k points

2 Answers

4 votes

Answer:

3/2y - 5

Explanation:

-1/2(-3y+10)

Expand the brackets.

-1/2(-3y) -1/2(10)

Multiply.

3/2y - 5

User Cybermotron
by
5.2k points
3 votes

Answer:


= ( 3y)/(2) - 5 \\

Explanation:

we know that,


( - ) * ( - ) = ( + ) \\ ( - ) * ( + ) = ( - )

Let's solve now,


- (1)/(2) ( - 3y + 10) \\ (3y)/(2) - (10)/(2) \\ = ( 3y)/(2) - 5

User Renee
by
5.0k points